Photocatalytic Activity and Mechanical Properties of Cement Slurries Containing Titanium Dioxide - Yasmine Jabali; Joseph Assaad; Georges Aouad (Buildings, 2023)
The effect of titanium dioxide (TiO2) on the mechanical properties of cement slurries including their benefits on air purification and abatement of pollutants is not well documented. Cementitious-based slurries are typically applied in thin layers as decorative coatings for existing facades, protection against an ingress of aggressive ions, or rainproof covers to minimize water penetration. Different parameters including the TiO2 concentration, dispersion time during batching, and applied thickness on top of existing mortar blocks are investigated in this paper. Tested properties included the flow, colorimetry, compressive/flexural strengths, bond to existing substrates, water absorption, and photocatalytic activity evaluated using an ISO 22197-1:2007 reactor. The results showed that the mechanical properties remarkably improved with TiO2 additions, up to 8% of the cement mass. This was attributed to two concomitant phenomena including a micro-filler effect that enhances the packing density and nucleation sites to promote strength development. The removal of nitrogen oxides from the atmosphere reached 92% when the TiO2 was added at a rate of 5% of the cement mass. Such data can be of particular interest to consultants and environmental activists searching for innovative materials capable of maintaining better ambient air quality in urban and modern cities.